The emerging family of CULLIN3‐RING ubiquitin ligases (CRL3s): cellular functions and disease implications. (2nd August 2013) - Genschik, Pascal; Sumara, Izabela; Lechner, Esther
<x xml:space="preserve">Abstract</x> Protein ubiquitylation is a post‐translational modification that controls all aspects of eukaryotic cell functionality, and its defective regulation is manifested in various human diseases. The ubiquitylation process requires a set of enzymes, of which the ubiquitin ligases (E3s) are the substrate recognition components. Modular CULLIN‐RING ubiquitin ligases (CRLs) are the most prevalent class of E3s, comprising hundreds of distinct CRL complexes with the potential to recruit as many and even more protein substrates. Best understood at both structural and functional levels are CRL1 or SCF (SKP1/CUL1/F‐box protein) complexes, representing the founding member of this class of multimeric E3s. Another CRL subfamily, called CRL3, is composed of the molecular scaffold CULLIN3 and the RING protein RBX1, in combination with one of numerous BTB domain proteins acting as substrate adaptors. Recent work has firmly established CRL3s as major regulators of different cellular and developmental processes as well as stress responses in both metazoans and higher plants. In humans, functional alterations of CRL3s have been associated with various pathologies, including metabolic disorders, muscle, and nerve degeneration, as well as cancer. In this review, we summarize recent discoveries on the function of CRL3s in both metazoans and plants, and discuss their mode of regulation and specificities.